GENETIC STUDIES OF F2 POPULATION FOR FIBER AND YIELD RELATED ATTRIBUTES IN GOSSYPIUM HIRSUTUM - FATIMA, A; SAEED, A; KHALID, MN; IMAM, MMF; RAFIQUE, MA; SHARIF, MS; IQBAL, N; TIPU, ALK; AMJAD, I (Biological and Clinical Sciences Research Journal, 2022)
Cotton (Gossypium hirsutum L.)is grown as a commercial crop throughout the world and it maintains the national economy of Pakistan. Genetic variation is ultimate necessity of plant breeder for the utilization of high yielding varieties to minimize the gap between production and demand. An experiment was conducted for the estimation of correlation, path coefficient analysis, principal component analysis and cluster analysis for yield components in cotton (Gossypium hirsutum L.). Four genotypes and twelve F2 hybrids planted in field by using the randomized complete block design with two replications.Collected Data was subjected to analysis of variance (ANOVA) to observed difference for all traits which showed significant differences among studied traits. Correlation studies revealed that boll weightand number of bolls per plantshowedstrong and positive correlation with seed cotton yield. Path coefficient analysis revealed that boll weight and number of bolls per plant had positive direct effects on seed cotton yield. Based on biplot analysis it was identified that FH-342 × FH-458 and AGC-501×VH-363 performed best for the boll weight,number of bolls per plant andseed cotton yieldattributes. Dendrogram revealed genotypes under study were grouped in three clusters. Hence, selection for these characters will help in selecting genotypes with high yield and traits which contribute directly in cotton yield enhancement.